Determination of lead and cadmium contaminations in UF-Cheese and yoghurt produced in Esfahan and GolpayeganPegah Dairy Processing Establishments - E Jaberi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
Milk is a complicated liquid that contains necessary components for the growth of mammalian neonate. Milk can get polluted by heavy metals such as lead and cadmium. In this study, the concentrations of lead and cadmium were measured in 12 yoghurt and 12 UF cheese samples produced in each of the Isfahan and Golpayegan-Pegah Dairy Processing Establishments. The samples were analyzed using atomic absorption spectrometry by furnace according to AOAC instruction. According to the results, lead concentrations (Mean ± SD) in yoghurt and UF cheese samples produced in Isfahan and Golpayegan-Pegah were estimated at 54.96 ± 35.21, 61.65 ± 19.62, 105.38 ± 59.09, 141.94 ± 63.44 μg/Kg, respectively. In the case of cadmium, the concentrations were determined as 19.03 ± 1.23, 16.84 ± 8.08, 53.79 ± 19.29, 37.67 ± 22.58 μg/Kg, respectively. Results revealed a significant difference (P≥0.05) in lead and cadmium concentrations among the cheese samples of the two Dairy Processing Establishments. However, lead and cadmium concentrations in all samples were within the international approved limit (200 ppb).